Digitalization of Motor Vehicle Taxes Through the SAPAWARGA Application - Saska, Mutasya Dzikri Al; Amanah, Aam; Wulandari, Sri (Indonesian Journal of Advanced Research, 2025)
Digital transformation in public services aims to improve efficiency and public compliance, including in the payment of Vehicle Tax (PKB). The West Java Provincial Government has implemented PKB digitalization through the Sapawarga application. This study uses a descriptive qualitative method to analyze the implementation of Sapawarga at the Cirebon City Samsat, the challenges faced, and improvement efforts. Data was collected through interviews, literature review, and archival documentation from the Samsat office. The findings reveal improved access and transparency; however, challenges persist in system integration, inadequate regulatory support, and low digital literacy. Improvement efforts include routine evaluations, employee training, infrastructure upgrades, public awareness campaigns, and system updates to enhance application security and performance.